Evaluation of the Strontium Isotope Ratios in Soil–Plant–Fruit: A Comprehensive Study on Vignola Cherry (Ciliegia di Vignola PGI) - Lisa Lancellotti; Veronica D’Eusanio; Daniela Manzini; Caterina Durante; Andrea Marchetti; Lorenzo Tassi (Foods)
This study investigates the potential of strontium isotopes as a geographical tracer for Vignola cherries. Despite several studies having employed this indicator to trace the origin of food products, the mechanisms underlying the fractionation and translocation of strontium from soil to edible parts remain poorly understood. In this study, the 91Zr/90Zr ratio was used as a normalization pair to correct measurements of 87Sr/86Sr and 88Sr/86Sr (δ88Sr). Soil, cherry branches, and fruit samples were collected from various producers and locations. Isotopic analyses were carried out using a double-focusing multi-collector–inductively coupled plasma/mass spectrometer (MC-ICP/MS). External correction was applied using the 91Zr/90Zr ratio, assuming both equal and different fractionation factors for Sr and Zr isotopes. Results from both correction models showed improved accuracy by accounting for fluctuations in instrumental mass bias. Regarding the translocation of strontium, the data indicate an increase in 88Sr of approximately 0.2‰ from soil to plant tissue. This trend was consistent across all sampled locations.